1974
DOI: 10.1111/j.1471-4159.1974.tb12191.x
|View full text |Cite
|
Sign up to set email alerts
|

PHOSPHOINOSITIDE METABOLISM IN RAT SUPERIOR CERVICAL GANGLION, VAGUS and PHRENIC NERVE: EFFECTS OF ELECTRICAL STIMULATION and VARIOUS BLOCKING AGENTS1

Abstract: Abstract— Paired vagus nerves, phrenic nerves or superior cervical ganglia from rats were incubated at 37 C for various times in a simple salt solution containing glucose and 32Pi. One of the pair was usually stimulated electrically for 30 or 60 min. Stimulation of vagus nerve for 30 min increased phosphate incorporation into all the phospholipids studied but the increase was significant only in the case of triphos‐phoinositide and diphosphoinositide. This increase was not accompanied by increased labelling of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

1975
1975
1992
1992

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Schacht & Agranoff (1972a) showed a 1.5-fold increase in labelling of diphosphoinositido and triphosphoinositide in goldfish brain after administration of pentylenetetrazol. White et al (1974) reported that stimulation of vagus nerve for 30min increased 32p incorporation into all phospholipids studied, but the increase was significant only for diphosphoinositide and triphosphoinositide. By contrast, Schacht & Agranoff (1972b) observed a decreased labelling of polyphosphoinositides with 32p.…”
mentioning
confidence: 92%
“…Schacht & Agranoff (1972a) showed a 1.5-fold increase in labelling of diphosphoinositido and triphosphoinositide in goldfish brain after administration of pentylenetetrazol. White et al (1974) reported that stimulation of vagus nerve for 30min increased 32p incorporation into all phospholipids studied, but the increase was significant only for diphosphoinositide and triphosphoinositide. By contrast, Schacht & Agranoff (1972b) observed a decreased labelling of polyphosphoinositides with 32p.…”
mentioning
confidence: 92%
“…The latter are present in significant concentrations in peripheral nerve, and may be largely associated with myelin (41). There has been continuing interest and controversy concerning the role that the turnover of specific inositolcontaining phospholipids may play in cation transport and neural transmission (40,41). The possibility that the decreased nerve free MI concentrations found in acute experimental diabetes may be associated with alterations in the metabolism of the MI-containing phospholipids would therefore merit examination.…”
Section: Introductionmentioning
confidence: 99%
“…The known metabolic fates of myoinositol in neural tissue include its incorporation into phosphatidyl inositol (39), the parent compound of the polyphosphoinositides (40). The latter are present in significant concentrations in peripheral nerve, and may be largely associated with myelin (41). There has been continuing interest and controversy concerning the role that the turnover of specific inositolcontaining phospholipids may play in cation transport and neural transmission (40,41).…”
Section: Introductionmentioning
confidence: 99%
“…In experimental diabetes there is a reduced concentration of free myo-inositol in sciatic nerve [4][5][6][7]. This may be important in the development of neuropathy since inositol lipid metabolism is involved in nerve impulse conduction [8,9]. The deficiency of free inositol has not been reported in nerves from diabetic patients, though the concentration of inositol was significantly reduced in cerebro-spinal fluid from diabetic patients with neuropathy [10].…”
mentioning
confidence: 99%